Quasi-Z-Source Inverter With Hybrid Energy Storage For Induction Motor Drive System - Muhammad, Masitah (2019)
The energy storage system (ESS) of many commercially available hybrid electric vehicle (HEV) or pure electric vehicle (EV) is composed of only battery packs with a bidirectional dc-dc converter connected to the high voltage DC bus. In order to further improve fuel consumption efficiency, topologies to hybridize ESSs for EVs and HEVs have been developed. With these various combinations of energy storage, one common feature can be seen; which is to efficiently combine one fast response energy storage device with high power density and slow response device with high energy density. In relation to this, the Quasi Z-source inverter (qZSI) topology has gained attention as an alternative to the conventional voltage source inverter (VSI) in many applications such as the electrical motor drive system. Apart from offering a single stage DC-DC-AC conversion, it offers a flexible way on how the hybrid energy storage (HES) can be introduced to the system. In this research, a new combination of battery/supercapacitor as HES with qZSI applied for the induction motor drive system is investigated. The method of interfacing the supercapacitor via bidirectional dc-dc converter is proposed with implementation of supercapacitor current control to support the battery as the main energy source. The system is designed and modelled together with the required voltage and current control and simulated at 15 kW and 1.1 kW power rating. For validation purpose, hardware experiment at a scaled down 1.1 kW power rating is also carried out. Both simulation and experiment results shows agreement to each other and the proposed method works satisfactorily to reduce the current stress on the battery around 75% at 15kW power rating and around 60% at 1.1kW power rating during acceleration and regenerative braking with overall satisfactory operation of the qZSI fed induction motor drive system. This work has contributes towards efficient hybrid energy storage system for motor drive system not only for the qZSI, but can also be applied for the conventional voltage source inverter (VSI) as well.